Analysis Of the Role of Corporate Social Responsibility (CSR) In Optimizing Company Zakat Management - Mohammad Ghozali; Khurun'in Zahro' (UPT Publikasi Ilmiah UNISBA, 2026)
This study analyzes the alignment between corporate zakat obligations and Corporate Social Responsibility (CSR) within the framework of Islamic law, particularly maqāṣid al-sharī‘ah. The objective of this research is to clarify the conceptual relationship between corporate zakat as a mandatory obligation and CSR as a corporate responsibility aimed at promoting social welfare. This study employs a qualitative research design using a literature review approach, drawing on secondary data from scholarly publications and conceptual studies. The findings indicate that CSR and corporate zakat share common normative foundations, emphasizing social benefit (maṣlaḥah), distributive justice, and the protection of public welfare. This conceptual convergence supports the argument that CSR can function as an institutional mechanism to strengthen zakat values when oriented toward genuine social objectives. The study implies that corporate zakat governance can be enhanced through an integrated CSR–zakat framework to improve systematic social contribution and community welfare.